Public Rewards and Innovation Policy: Lessons from the Eighteenth and Early Nineteenth Centuries. Issue 6 (November 2014) - Burrell, Robert; Kelly, Catherine
<x xml:space="preserve">Abstract</x> There has been renewed interest in recent years in using prizes and rewards to promote innovation. History has played a central role in public debates in the UK about the merits of such interventions, with the Longitude Prize 2014 being self‐consciously modelled on its eighteenth century precursor. Similarly, historical case studies have been used extensively in the scholarly literature in this area. However, it is striking that there has been little engagement with parliament's role generally in rewarding inventors in the eighteenth and early nineteenth centuries and how this formed part of a broader system of rewards. The article explores how this system operated and demonstrates that it formed an established part of the legal landscape for many decades. It considers the extent to which a more complete understanding of the historical use of prizes and rewards during the key period of Britain's industrialisation might inform current debates.